Конституційно-правове регулювання інституту депутатської недоторканності в державах-членах Європейського Союзу - Ніконорова, Н.Ю. (Часопис Київського університету права, 2009)
В данной статье проводится сравнительно-правовой анализ конституционных норм государств членов Европейского Союза, регулирующих гарантии осуществления депутатских полномочий, в частности, депутатский иммунитет, его сферу действия и ограничения. По итогам анализа изложены перспективы дальнейших исследований в этой области с целью усовершенствования и приведения данных положений отечественного законодательства в соответствие с европейскими стандартами. Ключевые слова: гарант осуществления депутатских полномочий, институт депутатского иммунитета, его объем и ограничения, европейские стандарты, конституционные нормы стран-учасниц европейского Союза. The comparative legal analysis of constitutional norms of the European Union member states is conducted in this article. These norms regulate the guarantees of implementation of deputy plenary powers and in particular deputy immunity, its scope and limitations. On results of analysis the prospects of further researches in this area are expounded with the purpose of improvement and bringing these positions of domestic legislation over in accordance with the European standards. Key words: The guarantees of implementation of deputy plenary powers; the institution of deputy immunity, its scope and limitations; the European standards, constitutional norms of European Union members.